Answer:
Step-by-step explanation:
Using Bayes' theorem, we have:
[tex]P(A|B)= \frac{P(B|A)P(A)}{P(B)}[/tex]
[tex]P(A|B)[/tex] is a conditional probability: the likelihood of event A occurring, given that B is true.
[tex]P(B|A)[/tex] is also a conditional probability: the likelihood of event B occurring, given that A is true.
P(A) and P(B) are the marginal probabilities of observing A and B, independently of each other.
We solve thus:
[tex]P(User|+) = \frac{P(+|User)P(User)}{P(+)}[/tex]
= [tex]\frac{P(+|User)P(User)}{P(+|User)P(User) + P(+|Non-user)P(Non-user)}[/tex]
= [tex]\frac{0.99 X 0.005}{0.99 X 0.005 + 0.01 X 0.995}[/tex]
= [tex]\frac{0.00495}{0.00495 + 0.00995}[/tex]
= [tex]\frac{0.00495}{0.0149}[/tex]
= [tex]0.3322[/tex] or [tex]33.22%[/tex]%
Therefore, if an individual tests positive, it is more likely than not (1 - 33.2% = 66.8%) that they do not use the drug.